PENGALAMAN AWAL DAPAT MENGUBAH EKSPRESI GEN DAN MEMPENGARUHI PERKEMBANGAN JANGKA PANJANG - Farah Ayu Maulidina; Debbie Susanti; Siti Kania (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2022)
New scientific research shows that environmental influences can actually affect whether and how genes are expressed. Thus, the old idea that genes are